Intravitreal Anti-vascular Endothelial Growth Factor Injection for Retinopathy of Prematurity: A Systematic Review and Meta-Analysis - Taher, Nada O.; Ghaddaf, Abdullah A.; Al-Ghamdi, Sarah A.; Homsi, Jumanah J.; Al-Harbi, Bandar J.; Alomari, Lugean K.; Almarzouki, Hashem S. (Frontiers in Medicine, 2022)
Background: Laser photocoagulation and/or intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections constitute the current standard treatment for retinopathy of prematurity (ROP). This systematic review and meta-analysis aimed to assess the efficacy and safety of intravitreal anti-vascular endothelial growth factor (anti-VEGF) monotherapy for retinopathy of prematurity (ROP) treatment using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Methods: We searched the Medline, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) databases. We included randomized controlled trials (RCTs) that compared intravitreal anti-VEGF monotherapy (e.g., bevacizumab, ranibizumab, aflibercept, and pegaptanib) with laser photocoagulation in preterm infants with ROP. We evaluated the rates of recurrence, treatment switching, retreatment, adverse events, and mortality. The risk ratio (RR) was used to represent dichotomous outcomes. Data were pooled using inverse variance weighting. The quality of evidence was assessed using the GRADE approach. Results: Seven RCTs (n=579; 1158 eyes) were deemed eligible. The pooled effect estimate showed a statistically significant reduction in adverse events in favor of anti-VEGF monotherapy (RR=0.17, 95% confidence interval [CI] 0.07–0.44). The pooled analysis showed no significant difference between the anti-VEGF and laser groups in terms of recurrence (RR=1.56, 95% CI 0.23–10.54), treatment switching (RR=2.92, 95% CI 0.40 –21.05), retreatment (RR=1.56, 95% CI 0.35–6.96), and mortality (RR=1.28, 95% CI 0.48–3.41). Conclusion: Anti-VEGF monotherapy is superior to laser photocoagulation for eyes with zone I ROP due to the significantly lower recurrence rate and fewer adverse events. However, it shows no clear advantage over retinal ablative therapy for eyes with zone II ROP since lower retreatment and treatment switching rates were noted in the laser group, although the safety margin favored anti-VEGF injection.